2022
DOI: 10.3390/ma15217717
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Autoclave Sterilization and Multiple Use on Implant Scanbody Deformation In Vitro

Abstract: In the intraoral scanner (IOS) impression technique for dental implants, a scanbody (SB) is connected to the implant and scanned. Poly(ether-ether-ketone) (PEEK) is a widely used material for SBs and it is recommended for single use. However, from the perspective of the Sustainable Development Goals, it is desirable to use these products multiple times. As SBs are used in patients’ mouths, proper sterilization is necessary for multiple uses. In the present study, the effect of autoclave treatment and connectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Therefore, when we received such a large distortion with the pre sterilization scan we assumed that the effect of the sterilization (only three cycles) in this area is eligible in relation to the distortion of the scan and this can explain why we received lower mean error for the post sterilization. It is worth mentioning that we could not nd in the current literature experiments that focus on the effect of post sterilization in a wide edentulous area but only with two implants [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when we received such a large distortion with the pre sterilization scan we assumed that the effect of the sterilization (only three cycles) in this area is eligible in relation to the distortion of the scan and this can explain why we received lower mean error for the post sterilization. It is worth mentioning that we could not nd in the current literature experiments that focus on the effect of post sterilization in a wide edentulous area but only with two implants [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…In our study we used a similar method and software as Kato et al did, we used titanium ISB and not PEEK and we did only three cycles of sterilization. When comparing pre sterilization to post sterilization we also received changes in the mean errors and inconsistency results regarding inter-implant distance that we already explained [39].…”
Section: Discussionmentioning
confidence: 99%
“…49 Nonetheless, multiple connections of the ISBs to the implants do not have any significant influence or cause deformation. 38 The location of the ISB is another significant parameter that is encountered in a number of relevant studies. Τhe location of the implant and consequently of the ISB influences the scanning trueness in distance deviations.…”
Section: Discussionmentioning
confidence: 99%
“…Wear may be caused by repeated clinical use and sterilization procedures; therefore, the manufacturers' instructions should be followed carefully 49 . Nonetheless, multiple connections of the ISBs to the implants do not have any significant influence or cause deformation 38 …”
Section: Discussionmentioning
confidence: 99%
“…Another study, Kato et al demonstrated that there were significant differences in the distance and angle when comparing Scanbody connected to the implant before and after the autoclave treatment. However, repeated connections with or without autoclave treatment did not have a significant impact on the surface texture values that were measured [ 22 ]. Behr M et al conducted a study to demonstrate the impact that sterilization and ultrasonic cleaning have on the resin cement interface of customized dental implant abutments.…”
Section: Discussionmentioning
confidence: 99%